A new DRIE cut-off material in SOG MEMS process. (1st April 2023) - Si, Chaowei; Fu, Yingchun; Han, Guowei; Zhao, Yongmei; Ning, Jin; Wei, Zhenyu; Yang, Fuhua
Abstract: The silicon on glasses process is a common preparation method of micro-electro-mechanical system inertial devices, which can realize the processing of thick silicon structures. This paper proposes that indium tin oxides (ITO) film can serve as a deep silicon etching cut-off layer because ITO is less damaged under the attack of fluoride ions. ITO has good electrical conductivity and can absorb fluoride ions for silicon etching and reduce the reflection of fluoride ions, thus reducing the foot effect. The removal and release of ITO use an acidic solution, which does not damage the silicon structure. Therefore, the selection of the sacrificial layer has an excellent effect in maintaining the shape of the MEMS structure. This method is used in the preparation of MEMS accelerometers with a structure thickness of 100 μ m and a feature size of 4 μ m. The over-etching of the bottom of the silicon structure caused by the foot effect is negligible. The difference between the simulated value and the designed value of the device characteristic frequency is less than 5%. This indicates that ITO is an excellent deep silicon etch stopper material.